Discovery of the potent non-steroidal glucocorticoid receptor modulator BAY 1003803 as clinical candidate. Issue 16 (15th August 2020) - Berger, Markus; May, Ekkehard; Rehwinkel, Hartmut; Schäcke, Heike; Neuhaus, Roland; Rottmann, Antje; Zollner, Thomas M.; Jaroch, Stefan
Graphical abstract: Abstract: We report on the discovery of the new clinical candidate BAY 1003803 as glucocorticoid receptor agonist for the topical treatment of psoriasis or severe atopic dermatitis. In the course of optimizing the amino alcohol series as a highly potent new non-steroidal lead structure, considerations were made as to how physicochemical properties and safety concerns relate to structural motifs. BAY 1003803 demonstrates strong anti-inflammatory activity in vitro paired with a pharmacokinetic profile suitable for topical application.